Implementation Of Religious Tourism Development In Improving The Welfare Of The People Of Gresik Regency Maqashid Syariah Perspective - Varach Cahya Quennara; Renny Oktafia (Cita konsultindo, 2024)
This research explores the potential of the tourism sector as a driver of community economy in East Java Province, with a focus on religious tourism at the tombs of Sunan Malik Ibrahim and Sunan Giri in Gresik Regency. The research aims to understand how the development of religious tourism can improve the welfare of local communities. Primary data was obtained through interviews with foundation administrators and traders at the site, as well as direct observation. The qualitative research method was used by data analysis using ATLAS.ti software. The results of the study show that the development of religious tourism, including the improvement of facilities and cleanliness, has a positive impact on PAD, employment, and the image of the location, although there are negative impacts such as congestion and decreased cleanliness. The development also affects merchants with a decrease in visitors but encourages promotional innovation. The community enjoys a more organized economy and environment, with religious values maintained through education and peer control. Recommendations for the future include a reduction in parking levies and increased cooperation between the government, the community, and the foundation's administrators.